Análisis de la cadena de valor comercial de mariscos frescos y congelados caso ciudad de Cuenca Azuay - Astudillo Solano, Paúl Míchel (2017)
A large proportion of populations who inhabit in coastal zones is dedicated to sea fishing of fish and sellfish, depending a social conglomerate amount, these products have a high nutritional value, and people living in Ecuador highlands are the deficit inhabitants of these nutrients produced by shellfish. In this case is considerate necessary to research the fish and shellfish value chain from Puerto Bolivar to Cuenca city. Therefore, three objectives has been developed: To describe all the stages of fish and shellfish value chain to Cuenca, identify the characteristics of fish and shellfish that are marketed by stages, and propose business strategies to improve the product final quality. For this reason a semi-structure interview has been designed to apply to artisan fishermen and commercial intermediaries oh shellfish in Cuenca randomly, with the territorial scope matrix several factors has been established which evaluated the governance level of some commercial agents. The LEARD methodology has been used to characterize the stages. The results were a value chain of relational type, with three stags and four agents. In Cuenca city >70% of shellfish comes from Puerto Bolivar in respect of prices which have an increase in their final value due to transport and the products condition adequacy, such as gutting, cleaning and freezing. The principal strategy is the commercial regulation in Puerto Bolivar and the improvement of hygienic conditions. Nevertheless, it is discussed wheter the food systems and the food security tend to be negative aspects, with the emphasis in the concerns of how the development of the human community needs foods with a high sustainable nutritional value and its relation with the sea fishing shortage and the aquaculture impact in the health of the basin ecosystem, it is necessary to consider these aspects of food security and the products of the sea, like a previous step in a process of diagnostic to start a process that mediate the sustainability of the operation of the products taken from the sea. The market of fishing products is immersed in a process of globalization and in an environment each time more competitive. On one side, new opportunities appear to the sector as it can be the development of the local and regional market with high rates of development in several countries in sustainable growth as Ecuador. Most of market chains in some developing countries like Ecuador generate informal business in vertical sense, one of these informal cases is the market of shellfish from the coast to the highlands. In this aspect the informal sector has come carrying out the role of absorbing and muffling the impact of an economic and social crisis which problematic is demanding a quick and effective solution, for both the informal sector and the community, organizing a the time, the public space and be able to offer a better quality of life for all the engaged people.